Percutaneous heart valve interventions: a South African perspective - Weich, H.; Doubell, A.F. (SA Heart Journal, 2017)
Valvular heart disease represents a significant health care challenge in South Africa, mainly due to the prevalence of rheumatic fever. This review discusses the recent advances in percutaneous heart valve treatment, including heart valve replacement, as an alternative to open prosthetic valve replacement and it’s relevance in South Africa. Balloon mitral valvotomy is discussed with emphasis on patient selection, management during pregnancy and management in the presence of left atrial thrombus. Further developments regarding the percutaneous treatment of mitral valve disease include percutaneous treatment of mitral incompetence by annuloplasty via the coronary sinus and edge-to-edge repair with the aid of a mitral clip. Transcatheter aortic valve replacement is the more developed procedure and two valves have the CE mark of approval. Both have good short to medium term data demonstrating efficacy but are technically difficult to insert, very expensive and patient selection remains a major problem. Their use is thus limited to patients turned down for conventional surgery. Percutaneous pulmonary valve replacement has good evidence to show efficacy but its use is largely limited to patients with degenerated pulmonary outflow tract conduits.